A structural perspective on the interactions of TRAF6 and Basigin during the onset of melanoma: A molecular dynamics simulation study. Issue 11 (14th June 2017) - Biswas, Ria; Ghosh, Semanti; Bagchi, Angshuman
Abstract: Metastatic melanoma is the most fatal type of skin cancer. The roles of matrix metalloproteinases (MMPs) have well been established in the onset of melanoma. Basigin (BSG) belongs to the immunoglobulin superfamily and is critical for induction of extracellular MMPs during the onset of various cancers including melanoma. Tumor necrosis factor receptor‐associated factor 6 (TRAF6) is an E3‐ligase that interacts with BSG and mediates its membrane localization, which leads to MMP expression in melanoma cells. This makes TRAF6 a potential therapeutic target in melanoma. We here conducted protein‐protein interaction studies on TRAF6 and BSG to get molecular level insights of the reactions. The structure of human BSG was constructed by protein threading. Molecular‐docking method was applied to develop the TRAF6‐BSG complex. The refined docked complex was further optimized by molecular dynamics simulations. Results from binding free energy, surface properties, and electrostatic interaction analysis indicate that Lys340 and Glu417 of TRAF6 play as the anchor residues in the protein interaction interface. The current study will be helpful in designing specific modulators of TRAF6 to control melanoma metastasis. Abstract : Key Findings Binding with tumor necrosis factor receptor‐associated factor 6 (TRAF6) helps to confer proper helical conformation of the transmembrane domain of Basigin protein. Lys340 and Glu417 of TRAF6 were found to be the major energetic contributors in interaction with Basigin. Glu417 was found to be buried deep in grove in the protein‐protein interaction interface, which makes it the most important residue involved in Basigin interaction.